Effects of joint motion constraints on the gait of normal subjects and their implications on the further development of hybrid fes orthosis for paraplegic persons - Yang, L.; Condie, D.N.; Granat, M.H.; Paul, J.P.; Rowley, D.I. (Journal of biomechanics, 1996)
In this study the effects of angular motion constraints of the lower limbs on the gait of normal subjects were investigated. An assessment orthosis was developed with a new hip coupling mechanism which allows its ratio of reciprocal flexion to extension to be altered. The knee and ankle joints of the orthosis could also be set to be free or locked in specific directions of angular motion in the sagittal plane. A total of 12 different orthosis configurations was tested on three normal subjects. The kinematic, kinetic and electromyographic (EMG) data were collected using the VICON system, two Kistler forceplates, foot switches and an eight channel EMG system. The physiological cost index of walking was assessed by measuring the heart rate and walking speed. It was found that (1) a higher hip flexion-extension ratio was associated with lower energy cost and faster walking; (2) allowing the knee to flex significantly reduced the energy cost and increased the walking speed; (3) allowing the ankle to plantarflex during early stance phase reduced the knee flexing moment. The implications of these effects on the further development of hybrid functional electrical stimulation orthotic systems are discussed.